Histological Changes in Liver and Pectoral Muscles of Broiler Chickens Slaughtered with and Without Naming of Allah - Tarek , Khenenou; Mohamed, Melizi; Omar, Bennoune; Hassina, Benzaoui; Messaouda, Ibrir (International Journal of Poultry Science, 2013)
Sixty six broiler chickens (Ross 308) 60 day of age were selected according to their average body weight (2600 g) from broiler flock. Chickens were divided in 2 groups. The first group were slaughtered according to the Islamic ritual and Allah’s name has pronounced. The second group was slaughtered but the name of Allah was not pronounced. Livers and pectoral muscle fragments were collected carefully set in a 10% formalin and sent to the histology laboratory. The main results of the current study could be summarized as follows: Histological changes observed in broilers chickens slaughtered without naming of Allah consist mainly on congestive areas localized in blood vessels of the liver and pectoral muscles in some cases focal edema have been observed. While the liver and pectoral muscles of broilers slaughtered with Islamic method showed normal structure and no congestion have been noticed.